ANALYSIS OF THE INFLUENCE FROM CR, EPS, ROE, DER ON STOCK PRICES AT BASIC INDUSTRY AND CHEMICAL SECTORS DURING YEAR OF 2017 - Mustaffa, Matrodji; Syabani, Mochammad (Dinasti International Journal of Economics, Finance & Accounting, 2021)
This research has been purposed to examine and analyze those influences from Current Ratio (CR), Earning Per Share (EPS) on Return on Equity (ROE), Debt to Equity Ratio (DER) on the stock prices of the Basic industry and Chemical sectors during year of 2017. The research Data used secondary data during the period of 2017. The Sampling method used purposive method, where its filtrated from a total of 69 basic industry and chemical sectors companies at Indonesia Stock Exchange in 2017 to only 51 companies which met the criteria as samples. The analytical method in this research was classic assumption test and multiple linear regression. The results showed if the EPS had a significant effect while CR, ROE and DER did not effect the stock prices from basic industry and chemical sectors.